Contextual mathematical problem solving of deaf students based on the montague stages. (April 2020) - Muhafidin, I; Nurlaelah, E; Hasanah, A
Abstract: This study aims to analyze the completion of contextual mathematics problems of deaf children based on Montague stages. this research was descriptive qualitative research. the data collection technique was in the form of tests, questionnaires, and interviews. The subject of this study was deaf class XI students in one of the Special Schools (SLB-B) in Kuningan, Indonesia. The results of this study were the students' ability to solve contextual math problems from 2 students namely one student has the ability to solve contextual math questions in sufficient categories and one in the low category.